PENGARUH BRAND REPUTATION DAN ONLINE CUSTOMER REVIEW PADA MEDIA SOSIAL TIKTOK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN MS GLOW PADA MAHASISWA - Risna Salsa Sabila; Adi Nugroho (Interaksi Online, 2026)
The issue of the MS Glow split has become a hot topic on social media, particularly TikTok,potentially influencing consumer perceptions of brand reputation and product purchasingdecisions. Furthermore, consumer reviews shared on these digital platforms are often usedas primary sources of information before consumers make purchasing decisions. This studyaims to determine the influence of brand reputation and online customer reviews on TikTokon purchasing decisions for MS Glow beauty products among college students. The studyemployed a quantitative explanatory approach with a survey method by distributingquestionnaires to 101 TikTok-using student respondents who had purchased MS Glowproducts, selected using a purposive sampling technique. This study employed consumerbehavior theory and data analysis techniques were conducted through validity tests,reliability tests, and simple linear regression using SPSS software. The results showed thatbrand reputation had a positive and significant effect on purchasing decisions. Meanwhile,online customer reviews were also shown to have a positive and significant effect onpurchasing decisions with a significant value.